Cyclocybe parasitica var. microspora var. nov. and two new records of family Strophariaceae (Agaricales, Basidiomycota) from India - KAUR, HARWINDER; Saini, MK; Shivani (Mushroom Research, 2021)
The diversity of Agrocybe and Cyclocybe species has been studied from the various habitats throughout the Punjab state from 2008 to 2012. Total 08 collections belonging to five taxa namely Cyclocybe parasitica var. microspora var. nov., C. parasitica, Agrocybe pediades, A. splendida, A. sacchari, are reported usually growing in caespitose clusters. Out of these, C. parasitica var. microspora var. nov., proposed as new variety. Â C. parasitica, A. sacchari forms new records for India and A. splendida is first time report from North India. A. pediades is being recorded for the first time from district Patiala, Punjab.UGC AND DST